Inertial Sensing in Sports - Witte, K.; Tiedemann, S. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
This chapter focuses on inertial sensors and their possible applications in sports. Based on the previous development, it can be expected that their use will increase more and more in the future due to their relatively uncomplicated manageability, especially in sports practice. In this way, it will be possible for the trainer or the athlete to record the performance-determining parameters immediately after the executed movement or even synchronously. IMUs can be used individually, e.g. in or on the body segment of interest, such as the hand or the foot, or in a device itself, such as a ball or a sphere. Depending on the number of IMUs used, partial or whole-body movements can be diagnosed.